Preoperative radiotherapy in patients with locally advanced esophageal squamous cell carcinoma: a narrative review - Lin, Yan; Wang, Shou-Feng; Liang, Huan-Wei; Liu, Yang; Huang, Wei; Pan, Xin-Bin (Frontiers in Oncology, 2025)
Neoadjuvant treatments play a crucial role in improving survival rates for patients with locally advanced resectable esophageal cancer. The CROSS and NEOCRTEC5010 trials have shown that neoadjuvant concurrent chemoradiotherapy significantly enhances survival compared to surgery alone. In contrast, the NeoRes and CMISG1701 trials indicate that while neoadjuvant chemoradiotherapy yields a higher histological complete response rate, it does not confer survival benefits over neoadjuvant chemotherapy. The recent JCOG1109 trial has demonstrated that neoadjuvant triplet chemotherapy offers a statistically significant overall survival advantage compared to doublet chemotherapy. However, combining doublet chemotherapy with radiotherapy did not show notable survival improvement compared to doublet chemotherapy alone. Additionally, neoadjuvant immunotherapy in conjunction with chemotherapy has shown a greater histological complete response rate compared to neoadjuvant chemotherapy, with comparable rates to neoadjuvant chemoradiotherapy. These findings have sparked debate regarding the necessity of radiotherapy in neoadjuvant treatment protocols. This review aims to elucidate the role of radiotherapy based on the current evidence and to assess ongoing and future trials that may address existing knowledge gaps. It will also underscore the challenges in making definitive recommendations about radiotherapy, particularly as technologies and treatment modalities continue to advance.